Structure Of Mahmud Zamakhari’s Work “Nukatu-L-I’rab” - Pardayev, Abduvali (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
The article discusses Ahmad ibn Mahmud ibn Abu Bakr Nuriddin Sobuniy, a great mutakallim (theologian) and jurist from ancient Bukhara. He was born in the early 6th/12th century and is recognized as one of the prominent figures in the Maturidi school of thought. Sobuniy contributed significantly to the fields of kalam (theology), fiqh (Islamic jurisprudence), and usul al-fiqh (principles of Islamic jurisprudence).